Asal Usul Rumus Dasar Transformasi Laplace - Wikaria Gazali (Engineering, MAthematics and Computer Science (EMACS) Journal, 2022)
This paper discusses the Origin of the Basic Formula of the Laplace Transform L{f(t)}=∫_0^∞▒〖e^(-st) f(t) 〗 dt=F(s). To obtain this model, the author derives the basic formula for the Laplace Transform from a Power Series. In this derivation, we use Euler’s number to the power of the function and the Maclaurin Series to obtain the derivation of the Basic Formula for the Laplace Transform where the Maclaurin Series is derived from the Taylor Series.